2022
DOI: 10.1111/1751-7915.14128
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing electrical outputs of the fuel cells with Geobacter sulferreducens by overexpressing nanowire proteins

Abstract: Protein nanowires are critical electroactive components for electron transfer of Geobacter sulfurreducens biofilm. To determine the applicability of the nanowire proteins in improving bioelectricity production, their genes including pilA, omcZ, omcS and omcT were overexpressed in G. sulfurreducens.The voltage outputs of the constructed strains were higher than that of the control strain with the empty vector (0.470-0.578 vs. 0.355 V) in microbial fuel cells (MFCs). As a result, the power density of the constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
(105 reference statements)
0
13
0
Order By: Relevance
“…Thus, a focus on current density should be the priority for future microfluidic MFC improvements, for example, by using other bacterial strains, including mixed-culture and genetically engineered EABs. 33,50 Other iterative improvements on the base-model MFC presented here can enable continuous advances by exploiting recent innovations including structured anodes, 4 3D scaffolded anodes, 49 use of biopolymer membranes and their functionalization, 51 carefully chosen metal electrodes, 52 ionomer electrode coatings, 53 and doping of anodic EABs with metals and other materials. 54,55 In addition, more standard methods can also be considered, such as the use of higher buffer concentrations and solution conductivity and cathodes with a higher reduction potential.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a focus on current density should be the priority for future microfluidic MFC improvements, for example, by using other bacterial strains, including mixed-culture and genetically engineered EABs. 33,50 Other iterative improvements on the base-model MFC presented here can enable continuous advances by exploiting recent innovations including structured anodes, 4 3D scaffolded anodes, 49 use of biopolymer membranes and their functionalization, 51 carefully chosen metal electrodes, 52 ionomer electrode coatings, 53 and doping of anodic EABs with metals and other materials. 54,55 In addition, more standard methods can also be considered, such as the use of higher buffer concentrations and solution conductivity and cathodes with a higher reduction potential.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it was also elucidated that the c ‐type cytochrome OmcS forms long‐protein filaments that can extend several micrometres away from the cell. In fact, there is evidence that these OmcS filaments are the nanowires that were previously thought to be formed by type IV pilus subunits and that were hypothesized to be conductive via overlapping π‐orbitals (Filman et al, 2019 ; Lovley and Walker, 2019 ; Wang et al, 2019 ; Wang, Hu, Dong, Shi, & Jiang, 2022 ). The export of these conductive structures is based on the type IV pilus production machinery, which might be the reason why they have been thought to be pilus subunits instead of cytochromes (Gu et al, 2021 ).…”
Section: Optimization Of Electroactive Anodic Biofilms At the Gene Levelmentioning
confidence: 99%
“…In a very recent study Wang et al ( 2022 ) also followed a classical genetic engineering approach. The authors aimed to determine the applicability of nanowire proteins in improving bioelectricity production by overexpressing them.…”
Section: Optimization Of Electroactive Anodic Biofilms At the Gene Levelmentioning
confidence: 99%
“…One key problem is decreasing biofilm activity with increasing biofilm thickness, mainly due to the mass and electron transfer limits within the biofilm. In this special issue, (Wang, et al, 2022b ) reported on their efforts to tackle this issue (at least to a certain degree) by using a synthetic biology approach. The authors overexpressed several nanowire subunits of Geobacter sulfurreducens and they found that the mutants could form 45% to 70% thicker biofilms.…”
Section: Emerging Applications Of Metmentioning
confidence: 99%